도시와 농촌의 삶의 질 지수 측정방안 연구 - 박대식 (한국농촌경제연구원, 2005)
The main purpose of this study was to develop the reliable and valid measurement of quality of life indices which can indicate overall quality of life gap between urban residents and rural residents. The major research methods of this study were the collection and analysis of existing related data, the E-mailed survey, field survey, and others. Descriptive statistics such as frequencies, percentage, mean were used to organize and summarize the data. Factor analysis was used as a major statistical method in the calculation process of weight values. Z-score calculation was used as a major standardization method for different measurement units. The quality of life indicator system in 2004 consists of 3 fields(rural welfare, rural education, regional development and activation of complex industry) and 88 indicators. The quality of life indicator system in 2005 consists of 3 fields(rural welfare, rural education, regional development and activation of complex industry) and 77 indicators. The measurement of urban and rural residents' quality of life indices was divided into two parts: subjective and objective ones. The subjective measurement of urban and rural residents' quality of life indices was developed by using quality of life satisfaction question items(8 and 19 ones). The weight values of quality of life satisfaction question items were based on the 40 specialists' opinions. The objective measurement of urban and rural residents' quality of life indices was divided into individual index method and total index method. The total index method was exemplified by using 11 objective quality of life indicators. The tentative quality of life indicator system in 2009 consists of 3 fields(rural welfare, rural education, regional development and activation of complex industry) and 115 indicators. Researchers: Dae-Shik Park, Sang-Jin Ma, Eun-Jung Shin E-mail Address: pds8382@krei.re.kr